2022
DOI: 10.3390/ijms23105590
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Elements Orchestrating Lactobacillus crispatus Glycogen Metabolism in the Vagina

Abstract: Glycogen in the female lower reproductive tract is a major carbon source for colonization and acidification by common vaginal Lactobacillus species, such as Lactobacillus crispatus. Previously, we identified the amylopullulanase encoding gene pulA of Lactobacillus crispatus to correlate with the ability to autonomously utilize glycogen for growth. Here, we further characterize genetic variation and differential regulation of pulA affecting the presence of its gene product on the outer surface layer. We show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
1
21
1
Order By: Relevance
“…Besides substrate degradation we also found differences between the regulation. Alpha-glucosidase activity of G. vaginalis was in this study also observed in cultures grown on glucose whereas we previously found L. crispatus amylopullulanase to be repressed in the presence of the products of glycogen degradation such as glucose, maltose or maltotriose (14).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Besides substrate degradation we also found differences between the regulation. Alpha-glucosidase activity of G. vaginalis was in this study also observed in cultures grown on glucose whereas we previously found L. crispatus amylopullulanase to be repressed in the presence of the products of glycogen degradation such as glucose, maltose or maltotriose (14).…”
Section: Discussionsupporting
confidence: 71%
“…Apart from the absence of catabolite repression, and the ability to degrade raw amylose, we identified a third characteristic that was found to be distinctive: unlike to what we previously found for L. crispatus (14), the Gardnerella amylolytic activity was mostly found in the extracellular environment and only to a minor extent cell-bound. This is not consistent with the presence of a C-terminal transmembrane domain in the candidate amylopullulanase gene.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations